Copper(II)-Catalyzed Oxidative Esterification of Substituted p-Cresols under Ligand- and Additive-Free Conditions - Zhang, Zhong-Nan; Huang, Jian-Gang; Zhai, Jiao-Jiao; Guo, Ying; Ji, Ya-Fei (Synlett, 2015)
A facile, atom-economical, and efficient Cu(OAc)2-catalyzed oxidative esterification of substituted p-cresols was developed with ambient air as the terminal oxidant. This ligand- and additive-free esterification protocol allows an environmentally benign and reagent-economical access to benzyl esters.
Keywords: copper catalysis; esterification; substituted p-cresols; ambient air; sustainable reaction